2019
DOI: 10.7554/elife.45399
|View full text |Cite
|
Sign up to set email alerts
|

One bout of neonatal inflammation impairs adult respiratory motor plasticity in male and female rats

Abstract: Neonatal inflammation is common and has lasting consequences for adult health. We investigated the lasting effects of a single bout of neonatal inflammation on adult respiratory control in the form of respiratory motor plasticity induced by acute intermittent hypoxia, which likely compensates and stabilizes breathing during injury or disease and has significant therapeutic potential. Lipopolysaccharide-induced inflammation at postnatal day four induced lasting impairments in two distinct pathways to adult resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 94 publications
4
19
0
Order By: Relevance
“…The present study focused on the impact of polyIC in adult male rats, highlighting the need for additional studies in females. However, the lack of sex differences observed in adults after neonatal inflammation (Hocker et al, 2019), suggest females would respond similarly to polyIC-induced inflammation. It is important to note pLTF in females is altered by cycling estrogen levels (Dougherty et al, 2017), which may also influence CNS inflammatory responses (Arakawa et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The present study focused on the impact of polyIC in adult male rats, highlighting the need for additional studies in females. However, the lack of sex differences observed in adults after neonatal inflammation (Hocker et al, 2019), suggest females would respond similarly to polyIC-induced inflammation. It is important to note pLTF in females is altered by cycling estrogen levels (Dougherty et al, 2017), which may also influence CNS inflammatory responses (Arakawa et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that early-life infection can alter sensory input to the central respiratory network, destabilizing breathing. Recently, Hocker et al (2019) revealed that one bout of LPS at P4 caused long-lasting impairments in the respiratory motor plasticity system.…”
Section: Inflammation and Hypoxia In Early Lifementioning
confidence: 99%
“…Long-term facilitation of respiratory motor output in the adult was impaired via the serotonin-dependent pathway but was reversible by the anti-inflammatory drug ketoprofen administered during adulthood. The adenosine-dependent pathway was also impaired but could be stimulated via adenosine agonists (Hocker et al, 2019).…”
Section: Inflammation and Hypoxia In Early Lifementioning
confidence: 99%
See 1 more Smart Citation
“…An increased understanding of the complex relationship between DNA methylation and site-specific modifications in respiratory neural control networks will advance our appreciation of the notably deleterious impact of early-life exposures to hypoxic stress on cardiorespiratory control. Additional translational studies of oxygen dysregulation (intermittent hypoxia and hyperoxia) combined with other recognized risk factors, such as infection/inflammation (Hocker et al, 2019;McDonald, Dempsey, & O'Halloran, 2020), are required to characterize fully the portfolio of potential drivers of epigeneticdependent and independent mechanisms of respiratory morbidity across the lifespan. Such translational studies will further shape our understanding of the pivotal role of oxygen dysregulation as a driver of cardiorespiratory malaise, with the potential to inform interventional strategies in the clinical setting.…”
mentioning
confidence: 99%